The function or interlocking compressed earth brick in building wall systems: A literature review - Eddy Syaizul Rizam Abdullah; Abdul Karim Mirasa; Habib Musa Mohamad; Hidayati Asrah (Zes Rokman Resources, 2020)
To achieve sustainable and green technology in construction, more alternative methods were produced to replace the conventional construction materials which lack concern on elements of sustainability especially on humans, economics, and the environment. The conventional bricks especially the Fired Clay Brick (FCB) consume and emit high energy due to the production process where the flaming process is involved. Also, high carbon emissions caused by combustion can contribute to the greenhouse effect. Thus, the Interlocking Compressed Earth Bricks (ICEB) is produced and acts as an alternative method in replacing the conventional bricks. ICEB gives more advantages in terms of cost, time, and sustainable development. The aim of this paper to present the latest and related research on the performance and effectiveness of ICEB for wall elements as a load-bearing structure. The review of literature on the ICEB give a positive impact before, during, and after construction. This paper also aware the public of the existence of the ICEB system in construction as well as a reference on future practices.